Load tests on residual soil and settlement prediction on shallow foundation - A. Viana da Fonseca (2001)
The design of shallow foundations is often considered in semiempirical methodologies that are based on linear and nonlinear models of behavior, mainly for settlement prediction purposes. In this paper, the applicability of such criteria is discussed, by analyzing the results obtained at an experimental site on a fairly homogeneous saprolitic soil derived from granite. This included a full-scale load test on a circular concrete footing together with in situ and laboratory tests. The information obtained in terms of strength and stiffness was integrated with the aim of refining some of the approaches based on the theory of elasticity. Emphasis was especially given to semiempirical methodologies based on results of standard penetration tests, cone penetration tests, plate loading tests, and triaxial tests on high-quality samples with the results from local instrumentation. Some of the well-established methods were tested and some parametrical and methodological adaptations are suggested that better fit the observed behavior.